3d+3=12-6d

Simple and best practice solution for 3d+3=12-6d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d+3=12-6d equation:


Simplifying
3d + 3 = 12 + -6d

Reorder the terms:
3 + 3d = 12 + -6d

Solving
3 + 3d = 12 + -6d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '6d' to each side of the equation.
3 + 3d + 6d = 12 + -6d + 6d

Combine like terms: 3d + 6d = 9d
3 + 9d = 12 + -6d + 6d

Combine like terms: -6d + 6d = 0
3 + 9d = 12 + 0
3 + 9d = 12

Add '-3' to each side of the equation.
3 + -3 + 9d = 12 + -3

Combine like terms: 3 + -3 = 0
0 + 9d = 12 + -3
9d = 12 + -3

Combine like terms: 12 + -3 = 9
9d = 9

Divide each side by '9'.
d = 1

Simplifying
d = 1

See similar equations:

| x+2(2)=16 | | -18x+12y=-18 | | 5x-6(4x-1)=8 | | 16=24-4t | | 4+x=-4+-1x | | 3(4d+1)-9d=6(-2m+5)-4 | | x-(2x+3)=-4 | | 2x^3+7x^2-7x-30=0 | | 2w+2(6w-6)= | | 5+3x=5x+7 | | 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 |

Equations solver categories